Misconception Analysis of Biology Education Students Using Diagnostic Three Tier Test on Genetics Material - Ananda Nurputri Azzahra; Eka Kartikawati (Proceedings Series on Social Sciences & Humanities, 2023)
Genetics is a branch of Biology that becomes the basic building blocks of Biology, because almost none of the development of biological science is based on the concept of genetics. However, until now Genetics is still considered difficult for students so that the opportunity for the emergence of an understanding of the concept of genetics that is different from the understanding put forward by experts. The difference in understanding can trigger misconceptions especially in Biology Education students as future teachers who need to master Genetics content. Therefore, efforts are needed to identify students' conceptions with diagnostic three tier test which is considered capable of providing information about misconceptions. This study aims to identify and analyze the misconceptions of Biology Education students on Genetics material. The sample used is a saturated sample, namely all Biology Education Semester 2 students of FKIP UHAMKA. The research method used is descriptive quantitative, which plays a role in data collection in the form of a percentage of student conceptions to be compared with predetermined criteria. The results of this study concluded that there were misconceptions from the 18th diagnostic three tier test of Genetics material by 50%. Of the four sub-materials, respectively, the highest misconceptions occurred in the substance of genetics by 54%, cell division by 51%, patterns of inheritance of traits by 49%, and mutations by 43%.